Efficiency Enhancement of Bredigite‐Structure Ca14Mg2[SiO4]8:Eu2+ Phosphor via Partial Nitridation for Solid‐State Lighting Applications. Issue 2 (9th November 2012) - Lee, Kyoung Hwa; Im, Won Bin; Ballato, J.
<x xml:space="preserve">Abstract</x> We have synthesized a partially nitridated Ca13.7Eu0.3Mg2Si8O32 (CMSN:Eu2+) using Si3N4 with a conventional solid‐state reaction and successfully determined the structural parameters by a combined Rietveld refinement method. The partial nitridation of Ca13.7Eu0.3Mg2Si8O32 (CMS:Eu2+) led to a large enhancement in the luminescence intensity, as much as 148%. From the Rietveld refinement results, the anisotropic changes of the lattice parameters were observed for the partially nitridated samples. By incorporating this phosphor + red phosphor with an encapsulant on an InGaN light‐emitting diode (LED) (λmax = 395 nm), white light with a color rendering index of 92 and a color temperature of 5320 K under 20 mA was obtained.